The Role of Financial Transparency and Green Innovation in Enhancing the Sustainability Performance of SMEs in Pontianak City - Mayasafitri, Rina; Febriati, Febriati (Akuntansi dan Teknologi Informasi, 2026)
Purpose –This study aims to examine the effects of financial transparency and green innovation on the sustainability performance of Micro, Small, and Medium Enterprises (MSMEs) in Pontianak City. This study specifically investigates whether transparent financial management practices and environmentally oriented innovation can enhance the sustainability performance of MSMEs. Methods – An explanatory quantitative approach through survey methods targeting MSME actors who utilize digital financial recording applications. Data are analyzed using multiple regression to test the causal relationships among variables. Findings - The results indicate that both financial transparency and green innovation have positive and significant effects on MSME sustainability performance. Financial transparency contributes to sustainability performance by strengthening accountability, improving decision-making quality, and enhancing stakeholder confidence. Green innovation also exerts a significant positive influence by improving resource efficiency, reducing environmental impacts, and strengthening business competitiveness. Furthermore, green innovation demonstrates a stronger effect than financial transparency, highlighting the growing importance of sustainability-oriented innovation in supporting the long-term performance of MSMEs. Implications - This study contributes to the growing body of literature on MSME sustainability by demonstrating that sustainability performance is influenced by both governance-related and innovation-related capabilities. In practical terms, MSMEs can adopt green innovation to improve business performance. For the Pontianak Office of Cooperatives and MSMEs as a partner, this research is expected to serve as a reference in designing coaching, training, and incubation programs that integrate financial transparency and green innovation. Originality - The novelty lies in the integrative model that combines two crucial factors, such as financial transparency and green innovation in driving MSME sutainability performance. By filling a regional empirical literature gap and offering a digital and green based practical approachm this study provides a contextual foundation for strengthening MSMEs more holistically.